Dynamic communication performance of TTN with uniform and non-uniform traffic patterns using virtual cut-through flow control - Faisal, Faiz Al; Rahman, M.M. Hafizur; Inoguchi, Yasushi (2014)
Tori connected Torus Network (TTN) is a 2D-torus network of multiple basic modules, where each basic module is a 2D-torus network that are hierarchically interconnected for higher-level networks. The static network performance and dynamic communication performance using wormhole (WH) flow control of TTN has already been studied earlier and shown to be good than that of other networks. In this paper, we evaluate the dynamic communication performance of TTN using the virtual cut-through (VCT) flow control under uniform and non-uniform traffic patterns; and also compare the result with the other networks as well as the wormhole flow control of TTN network. We found that VCT with the nonuniform traffic patterns for TTN yields much better performance than that of 2D Torus, 2D Mesh, TESH, STTN and even better than the WH flow of TTN network in terms of network throughput and latency.